Spiritual Behavior and Stress in Adolescents: An Initial Study - Sumiyati Tarniyah; Laili Nur Hidayati (Jurnal Keperawatan Indonesia, 2021)
Spirituality is often associated with mental health, including stress. Older people tend to have high rates of involvement in spirituality rather than young people. This study aimed to identify the relationship between spiritual behavior and the stress levels of 152 high school students, using a descriptive correlation research design. The data collection techniques involved a spiritual dimension scale questionnaire and the Depression Anxiety Stress Scale 42 (DASS 42). The data were analyzed using Spearman's rho correlation test. The results show that the spiritual behavior distribution was mostly in the moderate category (53.3%), and stress level distribution was primarily in the normal category (63.8%). The finding also revealed that there was no correlation between spiritual behavior and stress levels in high school students. These results may differ from the previous studies. Although stress in this group showed a normal category, their mental health needs to be considered given the amount of stressors adolescents may face. Abstrak Perilaku Spiritual dan Stres pada Remaja: Studi Awal. Spiritualitas seringkali dikaitkan dengan kesehatan mental, termasuk stres. Kelompok usia tua cenderung banyak terlibat dalam kegiatan spiritual dibanding kelompok usia muda. Penelitian ini bertujuan untuk mengidentifikasi hubungan antara perilaku spiritual dengan tingkat stres pada 152 siswa sekolah menengah atas, dengan menggunakan desain penelitian deskriptif korelasi. Teknik pengumpulan data menggunakan kuesioner skala dimensi spiritual dan Depression Anxiety Stress Scale 42 (DASS 42). Analisis data menggunakan uji korelasi Spearman's rho. Hasil penelitian menunjukkan bahwa perilaku spiritual mereka sebagian besar dalam kategori sedang (53,3%), dan distribusi tingkat stres terutama dalam kategori normal (63,8%). Penelitian ini mengungkapkan tidak ada hubungan antara perilaku spiritual dengan tingkat stres pada remaja. Hasil ini mungkin berbeda dengan banyak penelitian sebelumnya. Meskipun stres pada kelompok ini menunjukkan kategori normal, tetapi kesehatan mental mereka perlu diperhatikan mengingat banyaknya stresor yang mungkin dihadapi remaja. Kata Kunci: perilaku spiritual, remaja, stres